Comet assay on thawed embryos: An optimized technique to evaluate DNA damage in mouse embryos. (October 2017) - Rolland, L.; Courbiere, B.; Tassistro, V.; Sansoni, A.; Orsière, T.; Liu, W.; Di Giorgio, C.; Perrin, J.
Abstract: Our objective was to optimize the CA technique on mammal embryos. Materials and methods: 1000 frozen 2-cell embryos from B6CBA mice were used. Based on a literature review, and after checking post-thaw embryo viability, the main outcome measures included: 1) comparison of the embryo recovery rate between 2 CA protocols (2 agarose layers and 3 agarose layers); 2) comparison of DNA damage by the CA on embryos with (ZP +) and without (ZP −) zona pellucida; and 3) comparison of DNA damage in embryos exposed to 2 genotoxic agents (H2 O2 and simulated sunlight irradiation (SSI)). DNA damage was quantified by the % tail DNA. Results: 1) The recovery rate was 3, 3% ( n  = 5/150) with the 2 agarose layers protocol and 71, 3% ( n  = 266/371) with the 3 agarose layers protocol. 2) DNA damage did not differ statistically significantly between ZP − and ZP + embryos (12.60 ± 2.53% Tail DNA vs 11.04 ± 1.50 ( p  = 0.583) for the control group and 49.23 ± 4.16 vs 41.13 ± 4.31 ( p  = 0.182) for the H2 O2 group); 3) H2 O2 and SSI induced a statistically significant increase in DNA damage compared with the control group (41.13 ± 4.31% Tail DNA, 36.33 ± 3.02 and 11.04 ± 1.50 ( p  < 0.0001)). The CA on mammal embryos was optimized by using thawed embryos, by avoiding ZP removal and by the adjunction of a third agarose layer. Highlights: Retaining zona pellucida and using frozen embryos simplified the Comet Assay technique. The adjunction of a third agarose layer reduced embryo loss. The use of frozen embryos allows subsequent analysis if required. This new tool could be used to analyze DNA damage in embryos after in vivo or in vitro exposure.